Transforming the Educator Profile in the Society 5.0 Era: Between Teacher Competency Standards and the TPACK Gap - Putri, putri; Nizza Burdatul Hijjah; Moh. Faizin; Aziz, Yahya; Yudi, Usman (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
Advances in digital technology have transformed the role of educators from mere instructors to technology-based facilitators. However, this transformation is often hindered by the gap between educational policies and the actual capabilities of teachers in the field. This study aims to analyze the empirical gap between digital competency requirements and the reality of educators’ capabilities, as well as to assess the relevance of competency standards under Law No. 14 of 2005 in the Society 5.0 era. This study employs a qualitative method using a literature review approach. Data were analyzed descriptively and analytically by comparing the Technological Pedagogical Content Knowledge (TPACK) theoretical framework by Mishra and Koehler with the dynamics of curriculum change in Indonesia. The findings indicate a consistent “competency gap” from the KTSP era through the Merdeka Curriculum, where improvements in digital infrastructure have not been accompanied by substantial pedagogical transformation. An analysis of Law No. 14 of 2005 reveals that while aspects of professionalism have been addressed, the details regarding technological literacy remain general in nature, leading to a disconnect in the implementation of teacher training. This study concludes that revitalizing the educator profile requires a holistic strategy that integrates TPACK theory into national regulations so that the digital transformation of education is not merely technical but also addresses inclusive pedagogical aspects.